THE TECHNOLOGICAL REVOLUTION AND THE DYNAMICS OF ISLAMIC DA'WAH - Hafiz Mubarak; A. Wajid Muntaqa; Ali Mu'ammar Zainal Abidin; Didi Sudrajat; Abdul Wahab Syakhrani (Universitas Muhammadiyah Metro, 2022)
In Islamic teachings, the effort to carry out Islamic da'wah is an obligation, so that Islam is great because of the vital flow of da'wah. In this technological era, da'wah must be continued by exploiting technology. To complete this discussion, we have conducted a series of literature searches on many online publications, including book journals and websites. In order to obtain valid findings, a series of analyzes involving the tuning coding system and critical evaluation under phenomenology have been carried out. Finally, we believe that the findings include that all Muslims must become a preacher by having Islamic knowledge and skills in using technologically advanced da'wah facilities. Hopefully, this finding will complement the study of da'wah and the technological revolution in the future.